SIMILARITY AND NONSIMILARITY SOLUTIONS ON FLOW AND HEAT TRANSFER OVER A WEDGE WITH POWER LAW STREAM CONDITION - M. Ismoen; M. F. Karim; R. Kandasamy; R. Mohamad (Universitas Mercu Buana, Prodi S2 Teknik Mesin, 2015)
The similarity and non-similarity analysis are presented to investigate the effect of buoyancy force on the steady flow and heat transfer of fluid past a heated wedge. The fluid is assumed to be a Newtonian, viscous and incompressible. The wall of the wedge is an impermeable with power law free stream velocity and a wall temperature. Due to the effect of a buoyancy force, a power law of free stream velocity and wall temperature, then the flow field is similar when n = 2m - 1, otherwise is non-similar when n ≠ 2m - 1. The governing boundary layer equations are written into dimensionless forms of ordinary differential equations by means of Falkner-Skan transformation. The resulting ordinary differential equations are solved by Runge-Kutta Gill with shooting method for finding a skin friction and a rate of heat transfer. The effects of buoyancy force and non-uniform wall temperature parameters on the dimensionless velocity and temperature profiles are shown graphically. Comparisons with previously published works are performed and excellent agreement between the results is obtained. The conclusion is drawn that the flow field and temperature profiles are significantly influenced by these parameters.